Nanoindentation Response of Ion-Irradiated Fe, Fe-Cr Alloys and Ferritic-Martensitic Steel Eurofer 97: The Effect of Ion Energy - Das, Aniruddh; Altstadt, Eberhard; Kaden, Cornelia; Kapoor, Garima; Akhmadaliev, Shavkat; Bergner, Frank (Frontiers in Materials, 2022)
Nanoindentation of ion-irradiated nuclear structural materials and model alloys has received considerable interest in the published literature. In the reported studies, the materials were typically exposed to irradiations using a single ion energy varying from study to study from below 1 MeV to above 10 MeV. However, systematic investigations into the effect of self-ion energy are still insufficient, meaning that the possibilities to gain insight from systematic energy variations are not yet exhausted. We have exposed pure Fe, ferritic Fe-9Cr, martensitic Fe-9Cr and the ferritic-martensitic reduced-activation steel Eurofer 97 to ion irradiations at 300 °C using 1 MeV, 2 MeV and 5 MeV Fe2+ ions as well as 8 MeV Fe3+ ions and applied nanoindentation, using a Berkovich diamond indenter, to characterize as-irradiated samples and unirradiated references. The effect of the ion energy on the measured nanoindentation response is discussed for each material. Two versions of a primary-damage-informed model are applied to fit the measured irradiation-induced hardening. The models are critically compared with the experimental results also taking into account reported microstructural evidence. Related ion-neutron transferability issues are addressed.